Implementasi Load Balancing Untuk Manajemen Jaringan Sebagai Media Pembelajaran Blended Learning Menggunakan Metode NTH Multi Connection di SMP Negeri 51 Jakarta - Gilang Azis Ramadhan; Hadi Zakaria (CV. Multi Kreasi Media, 2022)
The need for internet access is currently very high, both to find information, articles and the latest knowledge. Many schools have integrated the internet network as a media to support Blended learning. One of them is SMP Negeri 51 Jakarta, which is an educational institution that makes the internet a necessity to support teaching and learning activities and Blended learning activities in schools. The problem faced by SMP Negeri 51 Jakarta today is that the available Bandwidth is still limited, so schools want a stable and reliable internet connection. Therefore, a solution arises for the manufacture of a Load Balancing system on the network available at schools by combining Bandwidth schemes from two internet sources that are the same or different.